Micro-processor Control System Design of SDA1 AC Drive Diesel Locomotive - ZHANG Dong-fang; XIAO Gong-bin; ZHOU Shao-yun (机车电传动)
Hardware constitution, technical specification and main functions of micro-processor control system for SDA1 AC drive diesel locomotive were introduced, as well as the design solution of low constant speed control. The practical operating result indicated that the design of micro-processor control system was reasonable and reliable, which completely met the design requirement.